Factors influencing language teacher cognition: An ecological systems study - Mohammadzadeh Mohammadabadi, Alireza; Ketabi, Saeed; Nejadansari, Dariush (Studies in Second Language Learning and Teaching, 2019)
Learning about language teacher cognition (LTC) is useful for understanding how language teachers act in the classroom. Employing an ecological framework, this study aimed to explore the factors influencing language teachers’ LTCs at different levels. To this end, qualitative data using semi-structured interviews and observation were collected from 62 (30 males and 32 females) Iranian EFL teachers. The results indicated that, at microsystem level, factors such as teaching equipment and facilities, teachers’ mood and feelings, their job satisfaction, and language proficiency influenced LTC. At mesosystem level, LTC was influenced by teachers’ prior learning experience, the collaboration and collegiality among teachers working in the language institute, teachers’ self-efficacy, and critical incidents that happened when teaching or learning. Additionally, the results indicated that exosystem level factors including teacher appraisal criteria, the teaching program and curriculum, and teacher immunity affected LTC. Moreover, LTC was subject to the influence of the government’s attitudes about ELT and religious beliefs about self and interaction, and friendliness with students at macrosystem level. More importantly, it was found that the factors influencing LTC were interrelated and interconnected and in several cases, LTC was a product of joint effect of several factors at various ecosystem levels. Finally, findings in this study suggest that language teaching programs provide recent educational technology in the classroom, foster collaboration and collegiality among teachers, and clarify teacher appraisal criteria for teachers in order to help create positive language teaching beliefs.